Socioeconomic differences in diet: An isotopic examination of post‐Medieval Chichester, West Sussex. Issue 4 (13th December 2019) - Dhaliwal, Kirandeep; Rando, Carolyn; Reade, Hazel; Jourdan, Anne‐Lise; Stevens, Rhiannon E.
Abstract: Objectives: Historical evidence suggests that social hierarchy pervaded all aspects of society in post‐Medieval England. This study uses stable isotope analysis to explore the extent to which socioeconomic status and sex affected the dietary habits of the inhabitants of post‐Medieval Chichester. Materials and Methods: Stable carbon and nitrogen isotope ratios were measured on 40 human burials from the post‐Medieval site of St. Michael's Litten (Chichester, West Sussex, England). Samples were selected from three burial types that denoted differing socioeconomic status with roughly equal numbers of males and females: tomb burials ( n = 13) for high‐status; single coffin burials ( n = 14) for middle‐status; and shroud burials ( n = 13) for low‐status individuals. Results: The data showed a largely terrestrial diet with the possibility of some inclusion of marine resources. The isotope results indicate significant variation in the consumption of terrestrial meat (and marine protein) between high‐status tomb burials and coffin and shroud burials, showing that socioeconomic status likely played a role in daily dietary patterns. However, the isotope data suggest sex did not influence an individual's diet. Discussion: These results mirror trends established in status‐based studies from elsewhere in post‐Medieval England. However, notably absent from the data is evidence for significant marine resource consumption, which is a well‐established dietary trend of the late Medieval and early post‐Medieval periods. These results indicate post‐Medieval Chichester was a socially stratified society with clear implications that the diet of higher status individuals differed significantly from lower status.